2012
DOI: 10.1590/s0102-695x2012005000095
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and leishmanicidal activity from leaves of Kielmeyera variabilis

Abstract: Abstract:Many phenolic compounds such as xanthones, quinones and coumarins have been isolated from Kielmeyera species; however the presence of flavonoids have been showed in other genera in the Calophylleae tribe as Caraipa, Mesua and Calophyllum. Six known glycosidic flavonoids: quercetin 3-β-O-galactopyranoside (1), quercetin 3-β-O-glucopyranoside (2), quercetin 3-O-α-rhamnoside (3), luteolin 6-C-β-glucopyranoside (4), isovitexin (5), kaempferol 3-O-α-rhamnoside (6) and one triterpene, lupenone (7) were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…40 Quercitrin was reported to have antiprotozoal activity (L. donovani: 17.7 μg mL −1 ; T. brucei rhodesiense: 27.9 μg mL −1 ; T. cruzi: >30 μg mL −1 ; L6: >90 μg mL −1 ), 38 and non-dose-dependent activity of isoquercitrin against L. amazonensis amastigotes (0.78-20 μg mL −1 , 40-45%) has been described recently. 41 Manjolin et al found the same mixed mechanism of inhibition as described above for fisetin 20 (L. donovani: 0.6 μg mL −1 ; T. brucei rhodesiense: 3.3 μg mL −1 ; T. cruzi: >30 μg mL −1 ; L6: 38.5 μg mL −1 ; 38…”
Section: Flavonoidsmentioning
confidence: 55%
“…40 Quercitrin was reported to have antiprotozoal activity (L. donovani: 17.7 μg mL −1 ; T. brucei rhodesiense: 27.9 μg mL −1 ; T. cruzi: >30 μg mL −1 ; L6: >90 μg mL −1 ), 38 and non-dose-dependent activity of isoquercitrin against L. amazonensis amastigotes (0.78-20 μg mL −1 , 40-45%) has been described recently. 41 Manjolin et al found the same mixed mechanism of inhibition as described above for fisetin 20 (L. donovani: 0.6 μg mL −1 ; T. brucei rhodesiense: 3.3 μg mL −1 ; T. cruzi: >30 μg mL −1 ; L6: 38.5 μg mL −1 ; 38…”
Section: Flavonoidsmentioning
confidence: 55%
“…These data indicated the presence of rutinose sugar moiety. The obtained 1 H and 13 CNMR data were compared to the reported data and the compound was identified as rutin (quercetin-3-O-α-L-rhamnosyl (1```à 6``) β-D-glucoside) 27 .…”
Section: Phytochemical Investigationmentioning
confidence: 99%
“…In this context, medicinal plants that have been applied in traditional remedies often represent promising sources of lead compounds for the development of new drugs (Oliveira et al, 2011). Within the last few years, considerable research interest has focused on screening plant extracts as potential sources of drugs for the treatment of leishmaniasis (Vila-Nova et al, Cota et al, 2012;Ramírez-Macías et al, 2012;Vila-Nova et al, 2012;Santos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%